Some Fixed Point Results in Function Weighted Metric Spaces - Awais Asif; Nawab Hussain; Hamed Al-Sulami; Muahammad Arshad (Journal of Mathematics)
After the establishment of the Banach contraction principle, the notion of metric space has been expanded to more concise and applicable versions. One of them is the conception of ℱ-metric, presented by Jleli and Samet. Following the work of Jleli and Samet, in this article, we establish common fixed points results of Reich-type contraction in the setting of ℱ-metric spaces. Also, it is proved that a unique common fixed point can be obtained if the contractive condition is restricted only to a subset closed ball of the whole ℱ-metric space. Furthermore, some important corollaries are extracted from the main results that describe fixed point results for a single mapping. The corollaries also discuss the iteration of fixed point for Kannan-type contraction in the closed ball as well as in the whole ℱ-metric space. To show the usability of our results, we present two examples in the paper. At last, we render application of our results.